Community Participation of Yogyakarta as Climate Resilience City (CRC) - Heribertus Jaka Triyana; Endah Rantau Itasari (Jambe Law Journal, 2019)
Community has played central roles for initiatives of the Local Resilience Action Plan (LRAP) toward Yogyakarta as Resilience Climate City (CRC) since 2012. This paper aims to ﬁnd out relevance of community participation using the Catholic Church and Islamic Youth organizations participation as the model for dissemination and education on CRC as part of global agenda for achievement of the sustainable development goals. This paper is a empirical legal research conducted through an extensive and in-depth analysis of relevance legal data, i.e. primary and secondary data. At the end, they were completed through in depth analysis of legal logic to sustain their correlation and attribution to the said indicators of availibility, accessibility, adaptability and acceptability based on localities’ contexts and perspectives in Yogyakarta city. This paper reveals two conclusions. First, Catholic Churches and Islamic Youth Organizations in Yogyakarta city have played role to educate and to disseminate CRC through its internal Church guidance of the arch Bishop of Semarang manifestation 2035 and intended speech from Islamic leaders. Secondly, internal driven motivation is one of fundamental Christian values has been effective to continuously manage house hold wastes, increase green Catholic life style, and to map potential climate vulnerabilities.